The Influence of Digital Marketing on Purchase Intention with Brand Awareness as a Mediating Variable - William S. Edwin (Universitas Ciputra Surabaya, 2023)
This study examines the relationship of digital marketing to purchase intention, and the relationship of digital marketing to purchase intention mediated by brand awareness. The digital marketing variable has 4 indicators, namely information recombination, accessibility, navigation interaction, and speed. The next variable, namely brand awareness, has 4 variables, which are brand familiarity, knowing or having heard of the brand, brand knowledge, and advertising. The last variable, namely purchase intention, has 3 indicators, namely interest, presence, and information. In this study, researchers used a purposive sampling technique to collect respondent, the population used was Ciputra University Surabaya students from class 2018 and 2019 majoring in International Business Management, in total there are 213 respondents collected as the sample. In this study, it was found that digital marketing on purchase intention is insignificant, meanwhile the mediating relationship between brand awareness and digital marketing and purchase intention is significant. This study can clarify the inconsistency from various previous studies related to the relationship of digital marketing and purchase intention. In this study, significant results were found if the mediating variable which is brand awareness was added to the relationship between digital marketing and purchase intention variables.